Effectiveness of the Implementation of the Development Planning Deliberation (Musrenbang) in Medan Helvetia District - Hasanah, Ade Irma; Arif Nasution; Adam (Universitas Medan Area, 2025)
This study aims to analyze the effectiveness of the implementation of development planning deliberations in Medan Helvetia District, as well as to analyze the factors that hinder the effectiveness of the implementation of development planning deliberations in Medan Helvetia District. The research method used in this study is descriptive data analysis with a qualitative approach. Data collection techniques used are interview, observation, and documentation methods. The results of this study indicate that the implementation of musrenbang in Medan Helvetia District has not been effective. This can be seen from the community participation in decision-making that is not channeled as a whole; the stages of the development planning submission process are quite long, so there is a reduction in the submission of proposals, and community negotiations with the government are also getting smaller and the lack of budget, and inadequate quality of human resources. Budget and human resource issues emphasize the importance of adequate budget support and competent human resources to prepare development planning in Medan Helvetia District effectively, efficiently, and with quality for the welfare of the community.